OPTIMALISASI SUPERVISI AKADEMIK BERBASIS EVALUASI DIRI GURU (EDG) SECARA KOLABORATIF MELALUI PEER OBSERVATION PADA SEKOLAH BINAAN DI KOTA YOGYAKARTA - Reni Herawati (LPPM UNY, 2016)
This school action research was aimed at optimizing the implementation of academic supervision based on collaborative self evaluation through peerobservation at SMA Negeri 10 Yogyakarta, SMA Muhammadiyah 6 Yogyakarta,dan SMA Sultan Agung Yogyakarta. It was done in two cycles through four steps: (1) planning, (2) acting, (3) observing, and (4) reflecting. The Data collection was conducted through questionnaires, observation, interviews, and documentation. The data was analyzed by using triangulation analysis. To gain the meaning of research success, the success indicator was decided by the level of teacher professionalism in implementing peer observation from 2 (two) dimensions: 1. teacher’s perception towards supervision, and 2. teacher’s competency. The analysis result gave the proof that peer observation resulted positive contribution for enhancing teacher’s professionalism measured by the betterment of teacher perception toward supervision: (1) Teachers felt comfortable; (2) Teachers were more motivated to decide the steps in improving learning activity; (3) Teachers felt as subjects not objects; (4) Teachers were participated in planning; (5) Teachers were participatedin analysis the result of supervision; (6) Teachers became open minded andmotivated; (7) Learning quality was improved; (8) Collegiality among teacher was well-built. Implementation of peer observation also gave significant improvement of teacher’s professionalism measured by four indicators: know how to do, can do, will do, and will grow with the result as follows: (1) ‘know how to do’ aspect resulted 33.3% increase from 66.7% became 100%; (2) ‘can do’ aspect resulted 58.3% increase from 33.3% to 92.7%; (3) ‘will do’ aspect gave good contribution as much as 36.1% from 59.7% to 95.8%; (4) Finally, ‘will grow’ aspect showed an 50% increasing from 44.4% to 91.4%. To sum up, the implementation of peer observation gained significant impact to omptimize the academic supervision